An intracellular targeted antibody detects EGFR as an independent prognostic factor in ovarian carcinomas - Braicu Elena I; Sehouli Jalid; Buckendahl Ann-Christin; Darb-Esfahani Silvia; Weichert Wilko; Schwabe Michael; Noske Aurelia; Budczies Jan; Dietel Manfred; Denkert Carsten (BMC Cancer, 2011)
Abstract Background In ovarian cancer, the reported rate of EGFR expression varies between 4-70% depending on assessment method and data on patient outcome are conflicting. Methods: In this study we investigated EGFR expression and its prognostic value in a cohort of 121 invasive ovarian carcinomas, using a novel antibody against the intracellular domain of the receptor. We further evaluated an association between EGFR, the nuclear transporter CRM1 as well as COX-2. Furthermore, we evaluated EGFR expression in ten ovarian cancer cell lines and incubated cancer cells with Leptomycin B, a CRM1 specific inhibitor. Results We observed a membranous and cytoplasmic EGFR expression in 36.4% and 64% of ovarian carcinomas, respectively. Membranous EGFR was an independent prognostic factor for poor overall survival in ovarian cancer patients (HR 2.7, CI 1.1-6.4, p = 0.02) which was also found in the serous subtype (HR 4.6, CI 1.6-13.4, p = 0.004). We further observed a significant association of EGFR with COX-2 and nuclear CRM1 expression (chi-square test for trends, p = 0.006 and p = 0.013, respectively). In addition, combined membranous EGFR/COX-2 expression was significantly related to unfavorable overall survival (HR 7.2, CI 2.3-22.1, p = 0.001). In cell culture, we observed a suppression of EGFR protein levels after exposure to Leptomycin B in OVCAR-3 and SKOV-3 cells. Conclusions Our results suggest that the EGFR/COX-2/CRM1 interaction might be involved in progression of ovarian cancer and patient prognosis. Hence, it is an interesting anti-cancer target for a combination therapy. Further studies will also be needed to investigate whether EGFR is also predictive for benefit from EGFR targeted therapies.